Systemic strategies for enhancing elementary school teachers’ competence in the use of instructional media in Kosovo - Alma Vorfi Lama; Akhmad Munir (EDUCARE Journal of Primary Education, 2025)
Elementary school teachers in Kosovo demonstrate positive attitudes toward instructional media, yet their classroom implementation remains limited. Structural constraints, unequal digital infrastructure, insufficient professional development, and weak teacher retention systems hinder the effective integration of instructional media, ultimately constraining pedagogical innovation and the quality of learning in elementary education. This study examines Kosovo primary teachers’ instructional media competency needs, identifies implementation barriers, and formulates effective enhancement strategies by analyzing teacher readiness and contextual constraints in integrating digital and non-digital media into classroom practice. This study employed a descriptive qualitative design involving purposively selected primary teachers, principals, and supervisors from urban and rural schools in Kosovo. Data were collected through interviews, observations, document analysis, and focus group discussions, and analyzed thematically to ensure credibility and contextual depth. This study concludes that teacher competence in Kosovo is shaped by interconnected structural, institutional, and motivational factors rather than individual capacity alone. Limited infrastructure, insufficient professional development, teacher attrition, and weak retention systems undermine learning quality. Despite positive attitudes toward innovation, inadequate educational ecosystems hinder implementation, highlighting the need for integrated, sustainable, and context-sensitive systemic reforms. The findings imply that education improvement in Kosovo requires systemic policy reforms, including sustained professional development, teacher retention strategies, curriculum renewal, and equitable digital infrastructure, to effectively translate teachers’ positive attitudes into improved instructional practices and learning quality.